THE ROLE OF METAPHOR IN THE WINGS OF DOVE FOR HENRY JAMES DYNAMIC COGNITIVE APPROACH - Assistant Lecturer. Seddeeqah Hadi Salhb Al-Quraishi (American Journals, 2023)
In the perspective of the dynamic Cognitive method, this thesis discusses the function of metaphor in the dove's wings. The difference and contrast between the two words is referred to by the notion of cognitive linguistics (thinking and experience), which combines thinking and meditation while cognitive combines experience and reality. Theory is a property of the mind, but experience is a property of reality. Consequently, the question of how mind and reality are related arises.A branch of linguistics known as cognitive linguistics analyses language in terms of concepts that underlie its forms and are sometimes universal and other times unique. It shares this relationship with semantics but differs from psycholinguistics, which uses scientific data from cognitive psychology to explain the mental mechanisms underlying the learning, storing, producing, and understanding of speech and writing.
Keywords: cognitive linguistics', convergent methods, dynamic Cognitive, The wings of the dove, The discursive approach.